Echovirus encephalitis and myositis in primary immunoglobulin deficiency. Issue 1 (January 1978) - Webster, A D; Tripp, J H; Hayward, A R; Dayan, A D; Doshi, R; Macintyre, E H; Tyrrell, D A
Abstract : Two children are described with primary hypogammaglobulinaemia and encephalitis associated with echovirus infection. One also developed a condition resembling dermatomyositis which improved after he was given infusions of plasma containing antibody to the echovirus. Although both died of their encephalitis, the course of the brain disease in one of them may have been prolonged by treatment with specific antibody. These cases, together with another briefly mentioned case in an adult with congenital hypogammaglobulinaemia and echovirus infection, indicate that these patients are particularly susceptible to echoviruses.